Information Revelation and Strategic Delay in a Model of Investment - Chamley, Christophe; Gale, Douglas (Econometrica, 1994)
The authors characterize the symmetric equilibria of an investment game with a pure informational externality. When the period length is very short, the game ends very quickly; with positive probability, an informational cascade (herding) causes an investment collapse. As the period length increases, the possibility of herding disappears. As the number of players increases, the rate of investment and the information flow are eventually independent of the number of players; adding more players simply increases the number who delay. In the limit, a period of low investment is followed by either an investment surge or a collapse. Copyright 1994 by The Econometric Society.